The Complexity of ASEAN Way and Norms in Addressing Islam-Rooted Conflicts in Southeast Asia - Damayanti, Rizki; Muttaqin, Zaenal (Nation State: Journal of International Studies, 2024)
This research aims to investigate ethno-religious conflicts in the Southeast Asia region with a focus on the role of religion (Islam), nationalism, and citizenship issues, as well as to understand the complexity of resolving these conflicts within the framework of ASEAN Way norms. This research combines qualitative approaches and policy analysis to provide a comprehensive picture of the interactions between conflict factors and regional norms. The research methodology includes analysis of ASEAN policy documents and case studies of selected conflicts in the region. Qualitative analysis will be used to explore community perceptions and experiences regarding conflict, while policy analysis will examine how ASEAN Way is reflected in conflict resolution efforts. Preliminary results show that religious factors and nationalism often trigger conflict, while citizenship issues can complicate the dynamics of conflict. The ASEAN Way, which emphasizes the principles of non-intervention, deliberation, and consensus, has limited impact in responding to ethno-religious conflicts. This research will provide insight into how the ASEAN Way can be improved to be more effectively respond the ethno-religious conflict in the region. The implications of this research can also help design more effective conflict resolution mechanism and support sustainable peace in Southeast Asia.